Pericyte and Vascular Smooth Muscle Death in Diabetic Retinopathy Involves Autophagy - Tom A. Gardiner; Alan W. Stitt (International Journal of Translational Medicine, 2022)
Diabetic retinopathy (DR) is the most common complication of diabetes and a major cause of vision loss worldwide. The premature death of the microvascular mural cells represents both a pathological hallmark of vasodegeneration in DR and a basis for therapeutic intervention to halt progression to the sight-threatening stages. Recent studies suggest that retinal microvascular mural cells, classed as pericytes in the capillaries and vascular smooth muscle cells in the larger vessels (VSMC), may undergo autophagy-dependent cell death during DR. The present investigation was undertaken to assess electron microscopic evidence for involvement of autophagy in mediation of cell death in the mural cells of the retinal vasculature, in eyes from human diabetic donors and diabetic dogs. All specimens examined showed widespread evidence of autophagosomes in processes of viable pericytes and VSMCs, and the membranous remnants of excessive autophagic activity in their “ghost cell” remnants within the vascular walls. Autophagy was termed “excessive” when it occupied the greater part of the cytoplasm in mural cell processes. This was notable in specimens from short-term diabetic donors with no evidence of basement-membrane thickening or mural cell loss, in which regions of mural cell cytoplasm filled with autophagic bodies appeared to be undergoing cytoplasmic cleavage. No equivalent evidence of autophagy was detected in the adjacent endothelial cells of the retinal vessels. We conclude that increased autophagy in the retinal pericytes and VSMCs is linked to the diabetic milieu, and over time may also act as a trigger for mural cell loss and progressive vasodegeneration.